Gaps in knowledge and practices of malaria prevention in Francophone African immigrants in Metropolitan Edmonton - Hanna, Taylor A.; Ahmed, Ali; Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Youssef; Petrick, Ryland; Vincent, Etienne; El Hafid, Mélanie; Hawkes, Michel T.; Ravi, Srilata; Gnidehou, Sedami (Malaria Journal, 2022)
Background Important knowledge gaps exist in the understanding of the management of the risks of imported malaria in Canada among Francophone immigrants from sub-Saharan Africa (FISSA). The aim of this cross-sectional study was to investigate the malaria related-knowledge, attitude and practices (KAP) of FISSA in Edmonton, where these immigrants are in an official minority language situation and the impact of language barriers on these factors. Methods A structured survey was used to examine the KAP of 382 FISSA in the Edmonton area from 2018 to 2019. Fisher’s Exact Test was applied to determine if there were associations between knowledge of malaria and different risk factors. Results Almost all FISSA (97%) had an accurate knowledge of fever as the key symptom of malaria. Interestingly, 60% of participants identified bed nets as a preventive method and only 19% of participants had accurate knowledge of malaria transmission. An accurate knowledge of symptoms was significantly associated with a high perceived risk of contracting malaria [odds ratio (OR) 4.33, 95% confidence interval (CI) 1.07–20.62]. Furthermore, even though 70% of FISSA had a high perceived risk of contracting malaria in endemic regions, only 52% of travellers had a pre-travel medical encounter. Importantly, language was not the predominant reason for not seeking pre-travel medical advice, although 84% of respondents chose French as their official language of preference when seeking medical advice. Having a French-speaking physician was correlated with satisfactory prevention knowledge (OR 1.96, 95% CI 1.16–3.35). With respect to health-seeking behaviour, 88% of respondents with a child < 5 years of age would seek medical care for fever in the child after travel to sub-Saharan Africa (SSA). Conclusion This study highlights that factors other than knowledge, risk assessment, and language might determine the lack of compliance with pre-travel medical encounters. It underscores the need for effective strategies to improve this adherence in minority settings.

Reconnaissance du travail des proches aidantes en contexte francophone minoritaire : l'expérience des Fransaskoises - Savoie, Elda; Corriveau, Hélène; Lanteigne, Isabel; Savoie, Lise; Albert, Hélène (Reflets, 2022)
Cet article présente une recherche qualitative visant à comprendre l’expérience des proches aidantes francophones en Saskatchewan, en Alberta et en Colombie-Britannique. Il s’agit d’une recherche qualitative réalisée grâce à une collaboration entre la Fédération provinciale des Fransaskoises et une équipe de chercheures de l’École de travail social de l’Université de Moncton au NouveauBrunswick. L’objectif principal de cette étude était de mettre en lumière les défis rencontrés au quotidien ainsi que les pistes de solutions afin d’améliorer le soutien apporté aux proches aidantes. L’article se concentre sur 31 entretiens individuels réalisés en Saskatchewan. Les résultats de ces entretiens démontrent l’ampleur des conséquences du rôle de la proche aidante sur la santé mentale et physique ainsi que ses conséquences financières. De plus, une analyse selon les régions habitées (rurales ou urbaines) sera présentée pour mettre en lumière, entre autres, les défis rencontrés et les conséquences engendrées par le rôle de proche aidante. Mots-clés : Proche aidante, francophone, région rurale, région urbaine, contexte linguistique minoritaire, conséquence financière, absence de ressources

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Research Component. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon. Executive summary - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Volet Recherche. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)

L’Abécédaire d’un cerveau en santé - Sensibilisation à la démence dans l’Ouest et le Nord. Volet Recherche. État des connaissances, ressources existantes et lacunes en matière de troubles cognitifs et de démence chez les francophones en Colombie-Britannique, en Saskatchewan, en Alberta et au Yukon. Rapport de synthèse - van Kemenade, Solange; Benhamadi, Bey; Michel, Jean Nephetaly; Moussard, Aline (RésoSanté Colombie-Britannique, 2022)